2021
DOI: 10.1101/2021.10.29.466375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opponent learning with different representations in the cortico-basal ganglia circuits

Abstract: While positive reward prediction errors (RPEs) and negative RPEs have equal impacts in the standard reinforcement learning, the brain appears to have distinct neural pathways for learning mainly from either positive or negative feedbacks, such as the direct and indirect pathways of the basal ganglia (BG). Given that distinct pathways may unevenly receive inputs from different neural populations and/or regions, how states or actions are represented can differ between the pathways. We explored whether combined u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 69 publications
(175 reference statements)
3
17
0
Order By: Relevance
“…underlies obsession-compulsion. Moreover, given that such a combination of opponent SR+IR systems actually performs well in certain dynamic environments and its implementation in the cortico-basal ganglia pathways appears consistent with various findings (Morita et al, 2022), this possibility can further explain why human is prone to OCD and even healthy people tended to show shorter memory trace for negative PEs in the previous study (Sakai et al, 2022). Besides, considering a recent finding that silencing of dorsal raphe serotonin neurons disrupts model-based control in outcome devaluation tasks (Ohmura et al, 2021), our model is in line with one of the suggested mechanisms of the effectiveness of selective serotonin reuptake inhibitors (SSRIs) for OCD that SSRIs re-engage the brain system for model-based control (Robbins et al, 2019).…”
Section: )) (E)supporting
confidence: 83%
See 4 more Smart Citations
“…underlies obsession-compulsion. Moreover, given that such a combination of opponent SR+IR systems actually performs well in certain dynamic environments and its implementation in the cortico-basal ganglia pathways appears consistent with various findings (Morita et al, 2022), this possibility can further explain why human is prone to OCD and even healthy people tended to show shorter memory trace for negative PEs in the previous study (Sakai et al, 2022). Besides, considering a recent finding that silencing of dorsal raphe serotonin neurons disrupts model-based control in outcome devaluation tasks (Ohmura et al, 2021), our model is in line with one of the suggested mechanisms of the effectiveness of selective serotonin reuptake inhibitors (SSRIs) for OCD that SSRIs re-engage the brain system for model-based control (Robbins et al, 2019).…”
Section: )) (E)supporting
confidence: 83%
“…These results reconcile the recent suggestion of memory trace imbalance in OCD (Sakai et al, 2022) with the long-standing suggestion that OCD is associated with impairment of model-based control (Gillan et al, 2016; Robbins et al, 2019), raising a possibility that opponent learning in modelbased (SR-based) and model-free (IR-based) controls underlies obsession-compulsion. Moreover, given that such a combination of opponent SR+IR systems actually performs well in certain dynamic environments and its implementation in the cortico-basal ganglia pathways appears consistent with various physiological and anatomical findings (Morita et al, 2022), this possibility can further explain why human is prone to OCD and even healthy people tended to show shorter memory trace for negative PEs in the previous study (Sakai et al, 2022).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations